Comparative analysis of the genome of the field isolate V86010 of the rice blast fungus Magnaporthe oryzae from Philippines - ZHU, Kun-peng; Bao, Jiandong; ZHANG, Lian-hu; YANG, Xue; LI, Yuan; ZHU, Ming-hui; LIN, Qing-yun; ZHAO, Ao; ZHAO, Zhen; Zhou, Bo; Lu, Guodong (Elsevier, 2017)
Genome dynamics of pathogenic organisms are driven by plant host and pathogenic organism co-evolution, in which pathogen genomes are used to overcome stresses imposed by hosts with various genetic backgrounds through generation of a range of field isolates. This model also applies to the rice host and its fungal pathogen Magnaporthe oryzae. To better understand genetic variation of M. oryzae in nature, the field isolate V86010 from the Philippines was sequenced and analyzed. Genome annotation found that the assembled V86010 genome was composed of 1 931 scaffolds with a combined length of 38.9 Mb. The average GC ratio is 51.3% and repetitive elements constitute 5.1% of the genome. A total of 11 857 genes including 616 effector protein genes were predicted using a combined analysis pipeline. All predicted genes and effector protein genes of isolate V86010 distribute on the eight chromosomes when aligned with the assembled genome of isolate 70-15. Effector protein genes are located disproportionately at several chromosomal ends. The Pot2 elements are abundant in V86010. Seven V86010-specific effector proteins were found to suppress programmed cell death induced by BAX in tobacco leaves using an Agrobacterium-mediated transient assay. Our results may provide useful information for further study of the molecular and genomic dynamics in the evolution of M. oryzae and rice host interactions, and for characterizing novel effectors and AVR genes in the rice blast pathogen